Bilateral posterior ocular segment coloboma, entropion and squamous cell carcinoma in buffaloes with oculocutaneous albinism: a clinical, ultrasound, microbiological, cytological, and histopathological evaluation - A.M.V. Lima; A.R. Fayad; B.M. Assis; C.A. Neves; N.C. Borges; F. Camargo; D.B. Martins; C.H.S. Oliveira; E. Perlmann; P.J.B. Queiroz; R.E. Rabelo; L.A.F. Silva (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The study of ocular lesions associated with oculocutaneous albinism (OCA) in buffalo contributes to understanding the impact of this condition on buffalo production. The aim of this article is to describe the multiple ocular alterations observed in two buffaloes with OCA. A 13-month-old Mediterranean-Jafarabadi male and an 8-year-old Mediterranean female underwent ophthalmic, ultrasound, microbiological, cytological and histopathological evaluation. The male showed entropion and coloboma of the retina, choroid, and sclera. The female presented a proliferation of neoplastic cells consistent with squamous cell carcinoma in the bulbar conjunctiva and third eyelid. Both animals had a Schirmer tear test between 25 and 35mm/min and intraocular pressure between 11 and 15mmHg. There was growth of Pseudomonas maltophilia, Enterobacter aerogenes, and Escherichia coli and Rhodotorula sp. in both samples collected from the conjunctival fornices. A variable number of epithelial cells, lymphocytes and neutrophils were identified by conjunctival cytology. No ultrasound changes were identified. In view of the findings, a complete ophthalmic examination of buffaloes with OCA is recommended as a way of investigating alterations that are not always obvious on remote inspection, as well as avoiding exposure to solar radiation to minimize the occurrence of ocular squamous cell carcinoma.